Gastric cancer: modern approaches and prospects of treatment for peritoneal carcinomatosis (literature review) - V. A. Markovich; S. A. Tuzikov; E. O. Rodionov; N. V. Litvyakov; N. O. Popova; M. M. Tsyganov; L. V. Levonyan; S. V. Miller; D. V. Podolko; I. A. Tsydenova; M. K. Ibragimova (Сибирский онкологический журнал)
Gastric cancer (gc) is one of the most common cancers worldwide. The majority of newly diagnosed gastric cancer cases present with distant metastases. Peritoneal carcinomatosis (pc) is the most unfavorable type of progression of primary gc, which occurs in 14–43 % of patients. The purpose of the study was to highlight modern approaches to the treatment of gc with pc. Material and methods. We analyzed 136 publications available from pubmed, medline, cochrane library, and elibrary databases. The final analysis included 46 studies that met the specified parameters. Results. The modern approaches to the treatment of gc with peritoneal carcinomatosis were reviewed, namely: cytoreductive surgery (crs), combination of cytoreductive surgery and hyperthermic intraperitoneal chemotherapy (crs/hipec); neoadjuvant intraperitoneal/systemic chemotherapy (nips) and pressurized intraperitoneal aerosol chemotherapy (pipac). The results of large randomized trials and meta-analyses were analyzed. Benefits and limitations of these trials were assessed. Conclusion. The peritoneal cancer index (pci) and the level of cytoreduction are two key prognostic factors for increasing the median overall survival. By reducing tumor volume through cytoreductive surgery, it is possible to allow tumor cells to re-enter the proliferative phase of the cell cycle and make them more sensitive to antitumor agents. The hematoperitoneal barrier is the main reason that prevents the effective delivery of drugs from the systemic bloodstream to the abdominal cavity, which is why the effect of systemic chemotherapy on peritoneal metastases is extremely limited. Intraperitoneal chemotherapy offers a more effective and intensive regional therapy, creating a so-called «depot» of a chemotherapy drug, thereby prolonging the effect of the administered drugs. Cytoreductive surgery combined with hyperthermic intraperitoneal chemotherapy (crs + hipec) using the combination of surgical resection, cytotoxic chemotherapy, hyperthermic ablation of the tumor and hydrodynamic flushing, is a promising approach in the treatment of gc with peritoneal carcinomatosis.